2017
DOI: 10.1371/journal.pone.0171605
|View full text |Cite
|
Sign up to set email alerts
|

Capecitabine and cisplatin (XP) combination systemic chemotherapy in heavily pre-treated HER2 negative metastatic breast cancer

Abstract: Purpose/Objective(s)After taxane and anthracycline failure, no standard chemotherapy regimen is established in metastatic breast cancer (MBC). Capecitabine and cisplatin (XP) combination shows promising results in gastrointestinal cancer, but there are relatively scarce data in MBC. We reviewed the clinical outcome of XP regimen in anthracycline and taxane resistant, heavily pretreated MBC patients.Materials/MethodsBetween Jan. 2010 to Feb. 2016, 48 HER2 negative MBC patients who failed anthracycline and taxan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…While several studies reported activation of the MEK/ERK cascade in response to cisplatin treatment in several forms of cancer, the consequence of such activation on cell survival remains controversial (26–32). Few studies reported the activation of GST gene expression by MEK/ERK signaling in breast cancer (3335). Up until the present study, regulation of Gstp1 expression in lung CSCs has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…While several studies reported activation of the MEK/ERK cascade in response to cisplatin treatment in several forms of cancer, the consequence of such activation on cell survival remains controversial (26–32). Few studies reported the activation of GST gene expression by MEK/ERK signaling in breast cancer (3335). Up until the present study, regulation of Gstp1 expression in lung CSCs has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…cisplatin is associated with dose-dependent side effects (5,6), including gastrointestinal reactions (7), bone marrow suppression (8), liver and kidney damage (9), ototoxicity (10) and neurotoxicity (11). renal toxicity is frequently encountered, with a clinical incidence rate of 25-35% (12)(13)(14). The side effects associated with cisplatin have limited its use and clinical efficacy (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin and capecitabine in combination have been demonstrated in gastrointestinal cancers and have shown promising results [ 41 , 42 ]. However, there remains to be limited data on capecitabine in metastatic breast cancers.…”
Section: Main Textmentioning
confidence: 99%
“…However, there remains to be limited data on capecitabine in metastatic breast cancers. A study carried out by Lee et al [ 41 ], demonstrated capecitabine and cisplatin in combination in anthracycline and taxane resistant, heavily pre-treated HER2 negative metastatic breast cancer, displayed clinical benefit with tolerable toxicity in patients. These findings suggest that the proposed combination may offer an option for patients displaying cancer progression after anthracycline and taxane treatment introduction and also showed promise for HR positive metastatic breast cancer patients.…”
Section: Main Textmentioning
confidence: 99%